LEGAL FRAMEWORK OF REPRESENTATIONS, WARRANTIES AND INDEMNITIES IN ENGLISH LAW - R. A. Fayzullin (Финансы: теория и практика, 2017)
The paper analyzes civil-law institutions of representations, warranties and indemnities in contracts of purchase and sale of shares or stakes as a merger and acquisition method, and gets an insight into the legal nature of these legal mechanisms from the standpoint of the English legislator and judicial precedents. The author has analyzed the main English law doctrines, identified features and specifics of representations, warranties and indemnities. The relevance of the subject is determined by the transboundary nature of mergers and acquisitions. The author provides examples of the implementation of the above legal institutions when concluding shares purchase contracts. The author has also analyzed the terminological features of representations, warranties, indemnities as well as the relationships arising in the implementation of provisions on representations, warranties, indemnities.